2015
DOI: 10.1002/eat.22401
|View full text |Cite
|
Sign up to set email alerts
|

Negative affect prior to and following overeating‐only, loss of control eating‐only, and binge eating episodes in obese adults

Abstract: Objective The objective was to examine the trajectory of five types of negative affect (global negative affect, fear, guilt, hostility, sadness) prior to and following three types of eating episodes (overeating in the absence of loss of control [OE-only], loss of control eating in the absence of overeating [LOC-only], and binge eating) among obese adults using ecological momentary assessment (EMA). Method Fifty obese adults (84% female) completed a two-week EMA protocol during which they were asked to record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
114
1
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 166 publications
(132 citation statements)
references
References 45 publications
14
114
1
3
Order By: Relevance
“…Prior studies have shown that state negative affect is linked with subsequent LOC eating [25, 7073] and palatable food intake [26, 74]. However, we found only pre-meal state anxiety, but not state, anger, confusion, depression or fatigue, explained the relationship between recent social stress and palatable food intake.…”
Section: Discussioncontrasting
confidence: 81%
“…Prior studies have shown that state negative affect is linked with subsequent LOC eating [25, 7073] and palatable food intake [26, 74]. However, we found only pre-meal state anxiety, but not state, anger, confusion, depression or fatigue, explained the relationship between recent social stress and palatable food intake.…”
Section: Discussioncontrasting
confidence: 81%
“…How NA changes after binge eating and purging, as well as the role of PA in bulimic symptoms, are less clear; however, results derived from a recent multilevel, autoregressive cross-lagged analysis of EMA data indicate that binge eating predicts subsequent decreases in NA at numerous time points across the day (Lavender et al, 2016). These results are consistent with those of within-day analyses that examined trajectories (i.e., temporal patterns of change) of NA and PA intensity ratings preceding and following eating disorder behaviors (Berg et al, 2015; Engel et al, 2007; Engel et al, 2013; Smyth et al, 2007) and suggest that binge eating reduces negative affect. Taken together, despite some remaining debate about post-binge eating and purging affective change (e.g., Haedt-Matt and Keel, 2011), these findings lend support to negative reinforcement models of bulimic behavior.…”
Section: Introductionsupporting
confidence: 85%
“…We expected a four-factor solution consistent with the dimensions specified by the PANAS-X (i.e., Fear, Guilt, Joviality, Self-Assurance; Watson et al, 1988; Watson & Clark, 1994). However, in line with previous analyses conducted in samples with disordered eating (Berg et al, 2013; 2015), we expected the item “disgusted” to load onto the Guilt factor. Model fit was evaluated using the confirmatory fit index (CFI), the Tucker–Lewis index (TLI), the root-mean-square error of approximation (RMSEA), and the standard root-mean-square residual (SRMR).…”
Section: Methodssupporting
confidence: 73%
“…Thus, a specific focus on assisting individuals in managing affective responses related to self-concept may be especially appropriate in the treatment of AN. Finally, this study, taken together with prior studies (Berg et al., 2013; 2015), provides some evidence that several disordered eating behaviors may serve similar functions across diagnostic groups. Therefore, treatment approaches targeting common processes, such as guilt or shame, could have a positive impact on a variety of maladaptive behaviors among different patient groups.…”
Section: Discussionsupporting
confidence: 60%